2021
DOI: 10.1146/annurev-arplant-080720-084456
|View full text |Cite
|
Sign up to set email alerts
|

Tuber and Tuberous Root Development

Abstract: Root and tuber crops have been an important part of human nutrition since the early days of humanity, providing us with essential carbohydrates, proteins, and vitamins. Today, they are especially important in tropical and subtropical regions of the world, where they help to feed an ever-growing population. Early induction and storage organ size are important agricultural traits, as they determine yield over time. During potato tuberization, environmental and metabolic status are sensed, ensuring proper timing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
93
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 160 publications
2
93
1
Order By: Relevance
“…Therefore, the patterns and mechanisms of tuber number is an important research target. Extensive research has focused on tuberization in recent decades (Navarro et al, 2011 ; Zierer et al, 2021 ), but less attention has been paid to subsequent developmental changes in tubers. We found that not all initiated tubers swelled continuously until harvest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the patterns and mechanisms of tuber number is an important research target. Extensive research has focused on tuberization in recent decades (Navarro et al, 2011 ; Zierer et al, 2021 ), but less attention has been paid to subsequent developmental changes in tubers. We found that not all initiated tubers swelled continuously until harvest.…”
Section: Discussionmentioning
confidence: 99%
“…Several leaf‐derived signals are involved in tuberization, including FT (FLOWERING LOCUS T) protein (Abelenda et al, 2014 ; Navarro et al, 2011 ), BEL (BELLRINGER‐1 like), mRNA Bel5 (Banerjee et al, 2006 ; Cho et al, 2015 ), miR156, and miRNA 172 (Bhogale et al, 2014 ; Martin et al, 2009 ). Environmental factors, such as photoperiod, light quality, temperature, water, and nutrient supply, influence tuber development (Suyala et al, 2017 ; Zierer et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identified Poan-specific gene families are enriched in GO terms such as “response to light density” and “response to UV-B”. Light quality and intensity is one of the important factors of tuberous root formation [ 63 ]. It is important for Poan to adapt to the light density.…”
Section: Discussionmentioning
confidence: 99%
“…This aspect has been addressed in recent articles (Paliwal et al, 2020; Vanlauwe et al, 2019) and will not be discussed in our review. Similarly, we will not address specific root traits related to root and tuber crops that play an important role for food security in sub‐Saharan Africa and were discussed in recent reviews (Duque & Villordon, 2019; Zierer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%